HOTEL MANAGEMENT AND BRAND ACHIEVEMENT : A STUDY OF HOTEL INDUSTRY ACHIEVEMENT - RUMAMBI, LEONID JULIVAN (ITB Journal Publisher, LPPM ITB, 2007)
Hotel industry is a form of an intense interaction between employee and consumer. When a hotel chooses to perform in a perfect manner, then every operational mistakes will be considered as a loss and lowered brand asset value in consumer’ mind. Therefore, it can be the most valuable asset of a company and it will not exist without a loyal and satisfied consumer who also respects the brand that is promoted by the company. In this case, a hotel can develop its market size and consumers’ growing rate by emphasizing best service to them. This approach surely gives more advantage than other marketing activities such as discount or promotion program. Besides, it costs cheaper to give a best service to hotel’s existing consumers than trying to get new ones. This article will explain further about the importance of a balance between marketing, operational, and brand asset value in hotel industry through hotel management.